Antioxidant and Fatty Acid Changes in Pomegranate Peel With Induced Chilling Injury and Browning by Ethylene During Long Storage Times - Valdenegro, Mónika; Fuentes, Lida; Bernales, Maricarmen; Huidobro, Camila; Monsalve, Liliam; Hernández, Ignacia; Schelle, Maximiliano; Simpson, Ricardo (Frontiers in Plant Science, 2022)
Pomegranate (Punica granatum) is a non-climacteric fruit with a high antioxidant content in arils and peels, of which 92% are anthocyanins and tannins. However, it is susceptible to chilling injury (CI), a physiological disorder concentrated in the peel. To understand the effects of modified atmosphere and ethylene in the responses to stress on the antioxidant quality of the fruit and composition of fatty acids in the peel under CI conditions, the exogenous ethylene treatments (0.5, 1.0 and 1.5 μg L-1), 1-methylcyclopropene (1-MCP; 1 μL L-1), modified atmosphere packaging (MAP:XTend™ bags), combined strategy MAP/1-MCP and packaged in macroperforated bags (MPB-control treatment) were evaluated. The assay was performed in cold conditions (2 ± 1 °C; 85% RH) to stimulate damage and was sampled for 120 d (+ 3 d at 20 °C). During cold storage, CI symptoms began at 20 d in MPB and at 60 d for all treatments with exogenous ethylene; CI symptoms were delayed up to 120 d in MAP, 1-MCP and the combined MAP/1-MCP treatment. Ethylene and MPB-control treatments induced significant lipid peroxidation, and oxidative damage. In contrast, MAP alone or in combination with 1-MCP successfully delayed CI symptoms. However, no significant differences were observed between treatments in fatty acid content, in the peel. oleic acid, linoleic acid, palmitic acid, but a significant loss was noted after 60 days of storage. Cold storage caused an increase in anthocyanin concentration in the peel and arils, increasing up to 12 times in the peel of the fruit treated with ethylene at the final stage of storage (120 d + 3 d at 20 °C), with nonsignificant differences of the tannin content in the peel. During long-term cold storage of pomegranate, MAP and 1-MCP treatments delay and reduce the appearance of CI symptoms. This long cold storage induces an decrease in the unsaturated/saturated fatty acid ratio, which is not reversed by any postharvest treatment. A higher unsaturated/saturated fatty acid ratio after 1-MCP treatments showed a protective effect in peel tissues. In addition, it was possible to increase the concentration of anthocyanins in the peel of cold-storage pomegranates treated with ethylene.